Living on the rocks: a new species of Stenanona (Annonaceae) from karst limestone forests of southern Mexico - Ortiz-Rodriguez, Andres Ernesto; Gómez-Domínguez, Héctor; Espinosa-Jiménez, Josefa Anahí; Ruiz-Sanchez, Eduardo; Ornelas, Juan Francisco; Brewer, Steven (Phytotaxa, 2018)
Based on morphological and phylogenetic evidence, a new species of Stenanona endemic to the karst limestone forests from southern Mexico is described and illustrated. The new species is placed in the Desmopsis-Stenanona clade and appears to be closely related to Stenanona migueliana and S. stenopetala, from which it differs in flower colour, petal margins, petal venation, sepal length and ovule arrangement. Phylogenetic relationships, evolution and conservation status of the new species are discussed.